Psychiatry and the DSM: Cracks in an epistemic empire - Botha, Ryan (PINS-Psychology in Society, 2024)
In this article it is argued that the ontological integrity of psychiatry as a medical science remains deeply problematic. Psychiatric practice and attendant descriptive methodology in the form of the Diagnostic and Statistical Manual of Mental Disorders (DSM) have come under mounting scrutiny and criticism. Some of the most strident criticisms of psychiatric practice and theory have come from within its esteemed quarters (see Szasz, 1970), and have been reinvigorated through a recent publication by Allen Frances, the head of the DSM-IV Task Force. The arguments put forward by Frances are not new but carry added significance in that they stem from one of the professions most revered voices. Frances’ heretical attack on psychiatry’s “bible”, the DSM, offers the reader a glimpse into the operations taking place within the “inner sanctum” of psychiatry, the DSM Task Force. It is argued that psychiatry’s co-option by Big Pharma is reflective of a form hegemonic alignment that is consistent with the historical and political functioning of the psy-complex in modern bureaucratic society. This article provides a brief historical review of psychiatry’s deployment under various political regimes as well as an analysis of the evolution of the DSM and its growing role in the proliferation of psychopathology. The paper closes with an ironic resolve by offering a new discursive architecture for the profession of psychiatry.